DINAMIKA KELOMPOKTANI TERHADAP MINAT GENERASI MUDA PADA KEGIATAN USAHA TANI PADI (Oryza sativa. L) DI KECAMATAN GANTAR KABUPATEN INDRAMAYU - Aceng Jujun Junaedi; Oeng Anwarudin; Maspur Makhmudi (Sekolah Tinggi Pariwisata Mataram, 2020)
Group dynamics is one way to attract the interest of young people today to be interested in agriculture, especially rice farming. The current Covid-19 pandemic, the younger generation can carry out farming activities to fill leisure activities due to the large-scale social restrictions policy (PSBB). This study aims to analyze the factors that simultaneously influence group dynamics and the interests of the younger generation, and formulate appropriate strategies to increase the interest of young people through group dynamics in rice farming activities. The study was conducted in Baleraja Village and Situraja Village, Gantar Subdistrict, Indramayu Regency in March to June 2020. The population in the study was 62 people who were members of the farmers group, all of whom were research respondents. The variables in this study are individual characteristics, social support, group dynamics and the interests of young people. Primary data collection using instruments in the form of questionnaires. Data were processed using descriptive analysis and path analysis techniques. The results of the study on the interests of the younger generation were in the medium category with a share of 51.6 percent. The interest of the younger generation is directly affected by group dynamics. The social environment has a direct effect on group dynamics and an indirect effect on the interests of the younger generation. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. group dynamics and interests of the younger generation. Primary data collection using instruments in the form of questionnaires. Data were processed using descriptive analysis and path analysis techniques. The results of the study on the interests of the younger generation were in the medium category with a share of 51.6 percent. The interest of the younger generation is directly affected by group dynamics. The social environment has a direct effect on group dynamics and an indirect effect on the interests of the younger generation. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. group dynamics and interests of the younger generation. Primary data collection using instruments in the form of questionnaires. Data were processed using descriptive analysis and path analysis techniques. The results of the study on the interests of the younger generation were in the medium category with a share of 51.6 percent. The interest of the younger generation is directly affected by group dynamics. The social environment has a direct effect on group dynamics and an indirect effect on the interests of the younger generation. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. The results of the study on the interests of the younger generation were in the medium category with a share of 51.6 percent. The interest of the younger generation is directly affected by group dynamics. The social environment has a direct effect on group dynamics and an indirect effect on the interests of the younger generation. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. The results of the study on the interests of the younger generation were in the medium category with a share of 51.6 percent. The interest of the younger generation is directly affected by group dynamics. The social environment has a direct effect on group dynamics and an indirect effect on the interests of the younger generation. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups. Strategies to increase the interest of young people can be done through strengthening group dynamics and developing the social environment. The development of the social environment can also be done to strengthen the dynamics of farmer groups.